2020
DOI: 10.1371/journal.pone.0227471
|View full text |Cite
|
Sign up to set email alerts
|

A smartphone-based test for the assessment of attention deficits in delirium: A case-control diagnostic test accuracy study in older hospitalised patients

Abstract: Background Delirium is a common and serious acute neuropsychiatric syndrome which is often missed in routine clinical care. Inattention is the core cognitive feature. Diagnostic test accuracy (including cut-points) of a smartphone Delirium App (DelApp) for assessing attention deficits was assessed in older hospital inpatients. Methods This was a case-control study of hospitalised patients aged �65 years with delirium (with or without pre-existing cognitive impairment), who were compared to patients with dement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The DelApp is a computerized, objective test of arousal and attention that is implemented on a smartphone and is for use in both the general population and ICU patients. Case-control studies show a high sensitivity and a moderate-to-high specificity of DelApp in the detection of delirium 235,236 .…”
Section: Delirium Assessment In the Icumentioning
confidence: 99%
“…The DelApp is a computerized, objective test of arousal and attention that is implemented on a smartphone and is for use in both the general population and ICU patients. Case-control studies show a high sensitivity and a moderate-to-high specificity of DelApp in the detection of delirium 235,236 .…”
Section: Delirium Assessment In the Icumentioning
confidence: 99%
“…26 More-over, smartphone-based tests have been successfully validated in screening for delirium and discriminating it from dementia. 27 One of the challenges for an algorithm for delirium aetiology was the inter-patient variability in causality, creating a potential tension between inclusivity and ergonomics. Our original study identified key points of difference in patient presentation that would help focus clinical enquiry while avoiding redundancy in questions.…”
Section: Discussionmentioning
confidence: 99%
“…As such these analyses are exploratory and should be considered hypothesis-generating rather than confirming. Data were derived from a case–control study of a software application for detecting attention deficits in delirium, and the recruitment and assessment methods are described in detail in the original study [ 20 ]. Briefly, patients were recruited from geriatrics and orthopaedics wards of the Royal Infirmary of Edinburgh and Glasgow Royal Infirmary, Scotland.…”
Section: Methodsmentioning
confidence: 99%
“…The reference standard assessment for delirium based on DSM-5 criteria was informed by the Delirium Rating Scale-Revised 98 [DRS-R98 [22]]. As part of the assessment several scales and cognitive tests were administered: The Observational Scale of Level of Arousal [OSLA, [23]], the Richmond Agitation-Sedation Scale [RASS [24]], the Short Orientation, Memory and Concentration Test [OMCT [25]] and the Abbreviated Mental Test [AMT10 [26]], MOTYB, Days of the Week Backwards, Counting Backwards from 20 to 1, and Digit Span [20].…”
Section: Assessments and Participant Groupingsmentioning
confidence: 99%